Effects of auxiliary heat on the interlayer bonds and mechanical performance of polylactide manufactured through fused deposition modeling - Ning Yu (Elsevier, 2021)
The inherent interfacial bonding formation of layers determines the quality of complex 3D parts fabricated using fused deposition modeling (FDM). The inferior and anisotropic mechanical properties of FDM parts prevent their industrial application. This research is aimed at enhancing the mechanical properties and reducing the mechanical anisotropy of FDM parts through an innovative auxiliary heating treatment. Polylactide (PLA), which is a distinct semicrystalline polymer commonly used in 3D printing, was selected to examine the enhancement of mechanical properties by implementing auxiliary heating treatment. When the auxiliary heating treatment is applied, the tensile strength of the FDM-printed PLA part increases from 38.4 MPa to 63.6 MPa, and the degree of mechanical anisotropy decreases from 0.51 to 0.22. The auxiliary heating treatment yields superior mechanical properties compared to those attained through post-thermal annealing. Auxiliary heating represents a kind of “in-situ” annealing strategy during FDM printing. Moreover, the auxiliary heating temperature is similar to the cold crystallization temperature (Tcc) of PLA and is the optimal processing condition to obtain superior mechanical properties. As indicated by the SEM and DSC methods, the interfacial bonding of adjacent strands and crystallinity considerably influence the mechanical properties of FDM-printed PLA parts. Therefore, the auxiliary heating approach has the potential to be applied in the fabrication of large FDM parts.